Species DNA Detection Using PGR Gene Genetic Markers in Chicken Nuggets: Species DNA Detection Using PGR Gene Genetic Markers in Chicken Nuggets - Sophian, Alfi (Indonesian Food Science and Technology Journal, 2021)
Species DNA detection using genetic markers of the PGR gene on chicken nuggets was carried out to see whether these genetic markers could be used to test species DNA detection in chicken nuggets food products. The test method used in this study is a real-time PCR test method using the SYBR green technique where the test results can be either Ct or Tm values ​​which indicate amplification or detection. The results of DNA isolation showed that the concentration and purity of the isolated DNA were in the range of 35.10 ng/µL – 36.10ng/µL with an average of 35,488 ng/µL. As for the purity value measured at the A260/A280 wavelength, the results were obtained with a purity range between 2,110 – 2,250 with an average of 2,165. For the results of real-time PCR amplification, the Ct value of the chest sample was at 24.50, the Ct LOD value was at 21.20 and the Ct value of the positive control was 27.10. For the Tm value of the busty sample at 81.10, the Tm LOD value at 81.20 and the positive control Tm value at 82.10. In a conclusion, in this study, genetic markers of the PGR gene can be used to test specific DNA detection of chicken species in chicken nugget products.